Headache and orofacial pain: A traffic-light prognosis-based management approach for the musculoskeletal practice - Greenbaum, Tzvika; Emodi-Perlman, Alona (Frontiers in Neurology, 2023)
Introduction: Headache (HA) is one of the most prevalent disabling conditions worldwide and is classified as either primary or secondary. Orofacial pain (OFP) is a frequent pain perceived in the face and/or the oral cavity and is generally distinct from a headache, according to anatomical definitions. Based on the up-to-date classification of the International Headache Society, out of more than 300 specific types of HA only two are directly attributed to the musculoskeletal system: The cervicogenic HA and HA attributed to temporomandibular disorders. Because patients with HA and/or OFP frequently seek help in the musculoskeletal practice, a clear and tailored prognosis-based classification system is required to achieve better clinical outcomes. Purpose: The aim of perspective article is to suggest a practical traffic-light prognosis-based classification system to improve the management of patients with HA and/or OFP in the musculoskeletal practice. This classification system is based on the best available scientific knowledge based on the unique set-up and clinical reasoning process of musculoskeletal practitioners. Implications: Implementation of this traffic-light classification system will improve clinical outcomes by helping practitioners invest their time in treating patients with significant involvement of the musculoskeletal system in their clinical presentation and avoid treating patients that are not likely to respond to a musculoskeletal based intervention. Furthermore, this framework incorporates medical screening for dangerous medical conditions, and profiling the psychosocial aspects of each patient; thus follows the biopsychosocial rehabilitation paradigm.